Menstrual Regulation in the Perspective of Islamic Fiqh: An Examination of Sharia Laws and Limitations - Naufal Rizky Fadhilah; Tasya Afrianti; M. Yusuf Alamsyah Hrp (ISNU Sumatera Utara, 2025)
This study discusses the study of fiqh on Menstrual Regulation or menstrual regulation as a form of Family Planning (KB) practice in an Islamic perspective. In the modern era, the regulation of the menstrual cycle through drugs or medical interventions is often used by women for the sake of health, pregnancy planning, and the implementation of worship. This raises questions about its validity in Islamic law. This research uses a qualitative method with a library research approach, namely by examining classical and contemporary literature, including the Qur'an, hadith, fiqh books, and fatwas from religious institutions. The results of the study show that Islam basically allows the use of family planning methods, including menstrual regulations, as long as it meets several fiqh requirements, including: does not cause harm to health, is carried out on the basis of legitimate needs, and does not contradict the principles of sharia. Fiqh principles such as la dharara wa la dhirar (no harm) and maqashid syariah (the purpose of sharia), especially in safeguarding the soul and offspring, are the legal basis that allows this action. Thus, Menstrual Regulation is acceptable in Islam as long as it is carried out with medical considerations and sharia ethics.